Impact of Market Capitalization on Gross Fixed Capital Formation In Nigeria : 1985-2020 - Musa, Ibrahim; Magaji, Sule; Adewale, Adesoji Titus (International Journal of Indonesian Business Review, 2023)
This study examined impact of market capitalization on capital formation in Nigeria for the period of 1985-2020. Data were collected from secondary sources. The model was estimated with ARDL-ECM technique. The variables analyzed are Gross fixed capital formation (GFCF), Market capitalization (MCAP), Number of deals (NOD), change in Value of transaction (CAT), All share index (ASI) and Total listed equities and government stocks (TLE). The unit root resultindicates that CAT, ASI and TLE are stationary at level I(0) while GFCF, MCAP and NOD arestationary at first difference I(1). The ARDL bound test for co integration confirms the existence of co integration among the variables under consideration. The ARDL_ECM parameter is negative(-) and significant which is-0.570142, this shows that 57% percent disequilibrium in the previous period is being corrected to restore equilibrium in the current period. Finally, in the long run all the variables have significant impact on gross fixed capital formation except TLE. It was noted that MCAP, NOD and ASI have negative statistically significant impact on gross fixed capital formation. However, CAT and TLE have positive statistically significant and negative statistically insignificant impact on gross fixed capital formation respectively in Nigeria. The study concluded that market capitalization had negative significant impact on gross fixed capital formation in Nigeria. Hence, recommended that there is need for government to create enabling environment to enhance market participation through transparent and accountability by regulatory authority. This will attract investors to invest in Nigeria capitalmarket and market capitalization will increase as well and capital formation becomes inevitable.